Covid as an immunosuppressive disease a Review - Hafsa Javaid Malik; Ifra Chaudhry (ITScience (Information Technology and Science), 2022)
The three symptoms of coronavirus disease (COVID-19) that patients most often mention are cough, fever, and shortness of breath. However, other significant illnesses that are frequently observed in COVID-19 patients (such as diabetes mellitus, hypertension, kidney disease, neurologic disorders, arterial and venous thromboembolism, and kidney disease) imply that the virus is specifically attacking the endothelium, one of the largest organs in the human body. We provide here a systematic and comprehensive analysis of both clinical and preclinical evidence in support of the idea that the endothelium is a major target organ in COVID-19 and give a mechanistic explanation for its systemic symptoms.